Short-Chain Fatty Acid Transporters: Role in Colonic Homeostasis - Sivaprakasam, Sathish (Compr Physiol, 2017)
Short-chain fatty acids (SCFA; acetate, propionate, and butyrate) are generated in colon by bacterial fermentation of dietary fiber. Though diffusion in protonated form is a significant route, carrier-mediated mechanisms constitute the major route for the entry of SCFA in their anionic form into colonic epithelium. Several transport systems operate in cellular uptake of SCFA. MCT1 (SLC16A1) and MCT4 (SLC16A3) are H(+)-coupled and mediate electroneutral transport of SCFA (H(+): SCFA stoichiometry; 1:1). MCT1 is expressed both in the apical membrane and basolateral membrane of colonic epithelium whereas MCT4 specifically in the basolateral membrane. SMCT1 (SLC5A8) and SMCT2 (SLC5A12) are Na(+)-coupled; SMCT1-mediated transport is electrogenic (Na(+): SCFA stoichiometry; 2:1) whereas SMCT2-mediated transport is electroneutral (Na(+): SCFA stoichiometry; 1:1). SMCT1 and SMCT2 are expressed exclusively in the apical membrane. An anion-exchange mechanism also operates in the apical membrane in which SCFA entry in anionic form is coupled to bicarbonate efflux; the molecular identity of this exchanger however remains unknown. All these transporters are subject to regulation, notably by their substrates themselves; this process involves cell-surface receptors with SCFA as signaling molecules. There are significant alterations in the expression of these transporters in ulcerative colitis and colon cancer. The tumor-associated changes occur via transcriptional regulation by p53 and HIF1α and by promoter methylation. As SCFA are obligatory for optimal colonic health, the transporters responsible for the entry and transcellular transfer of these bacterial products in colonic epithelium are critical determinants of colonic function under physiological conditions and in disease states.